Comparison of Length-Weight Relationship in Liza tade (Forskal) from Estuaries of the Southern Karnataka Coast by Multiple Regression Analysis - K.S., Udupa; M., Averel; Bevinahalli, Vinayak; Reddy, Aswatha; C.H., Raghavendra; A.R., Kumara Swamy (Fishery Technology, 2025)
Random samples of Liza tade were collected from Netravathi-Gurpur, Mulky, Kallyanpura, Mabukala and Gangolli estuaries in the years 2000, 2001 and 2002. Multiple linear regression technique with 1 dummy, variable for sex of fish was used to identify the homogeneity or otherwise of 2 length-weight relationships for each estuary and in 3 years after pooling length-weight data accordingly. In addition, isometric growth of 2 sexes was tested by t-test. Trend line graph was used to compare growth conditions in various length-weight relationships. The whole process is a substitute for Analysis of Covariance technique.